cGMP-Dependent Protein Kinase in Regulation of the Pulmonary Circulation - Gao, Yuansheng; Raj, J. Usha (Current Respiratory Medicine Reviews, 2006)
Cyclic GMP-dependent protein kinase (PKG) plays a central role in the responses of the pulmonary vasculature to nitric oxide, nitrovasodilators, and natriuretic peptides. In mammalian cells, PKG is present in two forms, PKG I and PKG II, and the type I isoform is the primary enzyme involved in cGMP-dependent regulation of cardiovascular function. PKG can mediate vasodilation by lowering cytosolic Ca2+ levels by stimulating calcium-activated potassium channels and by phosphorylating inositol 1,4,5-triphosphate receptor associated PKG I substrate (IRAG). PKG can also cause vasodilation by reducing the Ca2+ sensitivity of myofilments by directly stimulating myosin light chain phosphatases (MLCP) and by interfering with the inhibition of MLCP exerted by Rho kinase. Recent studies show that PKG activity is regulated by oxygen and may be an important mechanism involved in postnatal adaptation of the pulmonary circulation. In chronically hypoxic lungs, PKG-dependent activation of calcium-dependent potassium channels may be impaired and thus contribute to an abnormally high vasomotor tone. A decrease in PKG activity may also contribute to the tolerance that the pulmonary vasculature develops to nitric oxide after prolonged therapy with nitric oxide inhalation for persistent pulmonary hypertension of the newborn (PPHN). Thus, the PKG appears to have multiple roles in the pulmonary circulation that can be affected by pathological conditions. With an increasing understanding of the mechanisms of PKG actions, the development of more selective tools to target the PKG pathway may lead to potential therapy for pulmonary vascular disease.
Keywords: lung